ANALISIS TINDAKAN ILOKUSI DALAM FILM “SING”. - Sukmawati, Darumas Bunga (Dharmas Education Journal (DE_Journal), 2022)
Illocutionary act is one of the sub-fields studied in speech acts. Illocutionary acts can be studied in movies, one of which can be through the "Sing" movie. The movie has an interesting storyline and presents many of Buster Moon's dialogues containing illocutionary acts. The movie "Sing", which came out in 2016, was made by Illumination Entertainment. The purpose of this study was to determine the types of illocutionary acts, the most dominant type of illocutionary acts, and to explain the contribution of illocutionary acts used by Buster Moon in learning English. The data collection method was the documentation research method while the data collection technique used descriptive analysis. Researchers used descriptive qualitative research. The object of this study was the utterances of Buster Moon in the “Sing” movie. Based on Searle's theory (1979), there were five illocutionary acts used by Buster Moon, namely assertive, directive, commissive, expressive, and declarative. From these results, the writers can conclude that the directive was the most dominant illocutionary act used by Buster Moon in the "Sing" movie. Teachers can use this study as a teaching media to help their students learn more about illocutionary acts in English.